(untitled) (Global Journal of Human-Social Science, 2015)
The extent of social transformation of any socially discriminated people may be better judged from the social philosophies propounded by their great leaders like Gandhi and Ambedkar in modern India. Gandhi is dead, so are Ambedkar and Marx. However, neither their philosophies-Gandhism, Ambedkarism and Marxism are dead nor could they posthumously suppress to one another. Their philosophical axis-may be different and dialectical such as for example absolutism versus relativism, positivism versus phenomenalism and theological versus metaphysical but remain the far sighted discourse for the liberation and emancipation of dalit in India. Our study also reveals that the protagonists of Gandhism, Ambedkarism and Marxism are either eating their humble pie in the circumstances of their failures or feeling like fishes out of water in the company of other outdated philosophies for the cause of dalit at present. Further, the change agents like heart, mind, conscience, science, violence, non-violence, constitutionalism, religion, state and village perceived in Gandhism, Ambedkarism and Marxism could not break loose the thread of casteism.